The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/pat.5045
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an efficient ternary flame retardant system for rigid polyurethane foam based on bi‐phase flame retardant effect

Abstract: The flame-retardant rigid polyurethane foams (RPUF) were prepared by using modified ammonium polyphosphate (MAPP) combined with expandable graphite (EG) and dimethyl methylphosphonate (DMMP). The thermal stability, flame retardant property, and mechanical property of flame-retardant RPUF were evaluated based on thermogravimetric analysis (TGA), limiting oxygen index (LOI) test, cone calorimetry tests, scanning electron microscopy (SEM) and compressive strength tests. The results showed that an efficient ternar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…In order to characterize the graphitization degree of the sample, the ratio of peak area of D (1364 cm −1 ) peak and G(1594 cm −1 ) peak of Raman spectrum is usually used to indicate the graphitization degree of the sample. The smaller the I D /I G value is, the higher the graphitization degree of the sample will be 31 . Pure TPU I D / I G is 2.51, after different ZIF‐L were added, they have different degrees of lower ratio, the lowest I D /I G value of TPU2 is 2.19, it showed that the metal oxide produced by the decomposition of three ZIF‐L can promote the formation of graphite carbon in a certain extent and Co have better catalytic effect, which can improve the flame retardant performance of composite materials.…”
Section: Resultsmentioning
confidence: 99%
“…In order to characterize the graphitization degree of the sample, the ratio of peak area of D (1364 cm −1 ) peak and G(1594 cm −1 ) peak of Raman spectrum is usually used to indicate the graphitization degree of the sample. The smaller the I D /I G value is, the higher the graphitization degree of the sample will be 31 . Pure TPU I D / I G is 2.51, after different ZIF‐L were added, they have different degrees of lower ratio, the lowest I D /I G value of TPU2 is 2.19, it showed that the metal oxide produced by the decomposition of three ZIF‐L can promote the formation of graphite carbon in a certain extent and Co have better catalytic effect, which can improve the flame retardant performance of composite materials.…”
Section: Resultsmentioning
confidence: 99%
“…Expandable graphite (EG), it should be noted, has been widely applied in polymer as flame retardants, especially in rigid polyurethane foam (RPUF) [ 24 , 25 , 40 , 41 , 42 , 43 ], due to its low toxic, abundance, and high flame-retardant efficiency. The flame-retardant mechanism of EG is that it can immediately expand (150~300 times) at relatively low temperature, and then form a worm-like protective char layer in the condensed phase, which is an effective barrier to prevent heat and mass transfer [ 24 , 42 , 43 ]. However, the loose “graphite worm” residues are easy to collapse, which hinders the further improvement of the flame-retardant efficiency of EG.…”
Section: Progress Of Flame-retardant Pumentioning
confidence: 99%
“…However, the loose “graphite worm” residues are easy to collapse, which hinders the further improvement of the flame-retardant efficiency of EG. Therefore, EG was usually used with other flame retardants, such as inorganic hydrated compounds [ 24 , 25 ], P/N/Si-containing organic compounds [ 40 , 41 , 42 , 43 ].…”
Section: Progress Of Flame-retardant Pumentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in recent years, researchers have focused on finding synergistic effect of expandable graphite (EG) with other additive flame retardants [ 40 , 41 , 42 ] or nanofillers [ 43 , 44 , 45 ]. The main mechanism to improve the flame resistance is to increase the char yield [ 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%